Role of acute hemodilution in blood transfusion rate in patients submitted to scoliosis surgery: observational retrospective study - Nobre,Layana Vieira (2020)
Abstract Background and objectives: The study assessed the role of acute hemodilution in the blood transfusion rate in patients submitted to surgical treatment of scoliosis. Methods: Retrospective observational study performed at Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo (HC-FMRP-USP). Medical charts of patients submitted to elective correction of scoliosis between January 1996 and December 2016 were analyzed. Variables assessed were: age, weight, sex, presence of comorbidities, data regarding anesthesia and surgery, lab data, adverse events and blood transfusion rate. The final sample consisted of 33 procedures performed by the same anesthesiologist and same surgeon, divided into two groups: Hemodilution Group (n = 16) and Control Group (n = 17). Indication of acute normovolemic hemodilution was determined by patient refusal of blood transfusion for religious reasons. Results: The sample was statistically homogeneous and the groups were compared in terms of the attributes analyzed. The volume of homologous blood used by the Hemodilution Group was significantly lower than the Control Group (p = 0.0016). The percentage of patients who required transfusion was 12.5% in the Hemodilution Group, while it was 70.69% (p = 0.0013) in the Control Group. Upon hospital discharge, mean values of hemoglobin and hematocrit between groups did not present significant differences (p = 0.0679; p = 0.1027, respectively). Conclusions: Acute normovolemic hemodilution, in scoliosis correction surgeries, reduces blood transfusion rates, meeting patient needs without increasing adverse events or infection rates.